Culture and Identity : Japanese Intellectuals during the Interwar Years. - Rimer, J. Thomas (Princeton legacy library., 2014)
This collection of essays represents the first attempt in this country to examine systematically the nature and development of modern Japanese self-consciousness as expressed through culture. The essays reveal eloquently the extent to which important aspects of Japanese intellectual life in the early twentieth century were inspired by European models of cultural criticism, ranging from Kant and Hegel to Nietzsche, Marx, Durkheim, and Bergson. Implicitly comparative, this collection raises the question whether ""late"" industrialization and related processes call forth cultural convergence).